2022
DOI: 10.1097/coh.0000000000000777
|View full text |Cite
|
Sign up to set email alerts
|

HIV and chronic lung disease

Abstract: Purpose of reviewAs people living with human immunodeficiency virus (HIV, PLWH) age, aging-related comorbidities have come into focus as major challenges to their overall health. In this review, an in-depth overview of the two most commonly encountered chronic lung diseases in PLWH, chronic obstructive pulmonary disease (COPD) and lung cancer, is provided. Recent findingsThe risk for both COPD and lung cancer remains significantly higher in PLWH compared to the HIVuninfected population, although fortunately ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 169 publications
0
1
0
Order By: Relevance
“…Alcohol use should be discouraged in patients with HIV as it is known to increase the risk of hepatotoxicity and fibrosis progression [ 41 ]. Patients living with HIV with lung disease (with HIV and co-existing lung disease), specifically chronic obstructive pulmonary disease and lung cancer, have an increased burden of disease (morbidity) and a poorer survival rate [ 42 ]. Living with a diagnosis of HIV while experiencing certain demographic and clinical characteristics, such as binge drinking, compulsive sexual behavior, polysubstance use, intimate partner violence, and depression, have a significantly decreased quality of life [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…Alcohol use should be discouraged in patients with HIV as it is known to increase the risk of hepatotoxicity and fibrosis progression [ 41 ]. Patients living with HIV with lung disease (with HIV and co-existing lung disease), specifically chronic obstructive pulmonary disease and lung cancer, have an increased burden of disease (morbidity) and a poorer survival rate [ 42 ]. Living with a diagnosis of HIV while experiencing certain demographic and clinical characteristics, such as binge drinking, compulsive sexual behavior, polysubstance use, intimate partner violence, and depression, have a significantly decreased quality of life [ 43 ].…”
Section: Reviewmentioning
confidence: 99%
“…17,18 Part of this heterogeneity is due to differences in COPD classification methods, such as self-report, International Classification of Diseases (ICD) diagnostic codes, use of CT scans, and spirometry. 17,19 For example, a systematic review and meta-analysis by Bigna et al evaluating the global prevalence of COPD among PWH found that the prevalence varied from 5.6% to 10.6% depending on the diagnostic criteria used, with a higher prevalence when using spirometric criteria instead of self-report or ICD diagnostic codes. 4 Geography COPD in PWH occurs anywhere PWH reside.…”
Section: Introductionmentioning
confidence: 99%